Available DSpace Repositories in Nepal: Describing their Local Adoptions - Nyaichyai, Lila (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
Digital library making has been basic requirements for the modern libraries. Instead of documents in papers, information is acquired and managed in some digital platform. One of the digital library platforms is DSpace, started in 2002. The collection of digital documents in DSpace is named DSpace repository. The main collection in DSpace repository is institutionally generated digital documents; hence, it is also synonymously termed as institutional repository. This study explored the existing Institutional Repository System (IRS) that was built in DSpace software in Nepal. Nepal, in South Asia, developed IRS in 2009. Literature suggested extensive studies about IRS in other South Asian countries, while Nepal was reported rarely. Moreover, Nepal was described as scanter than reality. There are nine IRS built-in DSpace in Nepal, enriching the collection from 101 to 15218. Except for three IRS, all other five IRS have their customized userinterface. They are on the way to improving their collection. Open Learning Education (OLE) Nepal has the highest collection and has diversified types of collections for kids. It is developed as Children's Digital Library. Except for three IRS, all are academic. So, these IRS have accommodated documents for academic purposes. They served students, teachers, researchers, and scholars.